Comparative efficacy of concurrent training types on lower limb strength and muscular hypertrophy: A systematic review and network meta-analysis - Chen, Y.; Feng, X.; Huang, L.; Wang, K.; Mi, J. (Journal of Exercise Science & Fitness, 2024)
Objective This study aims to compare, through quantitative analysis, the effectiveness of different endurance training types on increasing lower limb strength and muscle cross-sectional area (MCSA) in concurrent training.